Studying the mechanisms of formation and development of overweight and obesity for diagnostic information system of obesity - Vуsotska, Olena; Dobrorodnia, Hanna; Gordiyenko, Nina; Klymenko, Viktoriia; Chovpan, Ganna; Georgiyants, Marine (Eastern-European Journal of Enterprise Technologies, 2016)
The structure of the semantic attribute spaces is developed. The resulting space reflects an ordered presentation of variability for obesity process considering somatotype of person. This allows to consistently deepen body shaping process in detail and obtain a continuous transition from one type of metabolic disorders to another. This contributes to more accurate preclinical diagnosis and its taxonomy. It was determined in operation that a measure of deviation from the normal structure of the somatotype of biological development is measured in fractions sigma deviation. It is a characteristic of formation in obesity and helps to explain the mechanisms of its development. The range of one sigma deviation corresponds to the functional optimum of somatic type variation. The research results can be used to trace individual dynamics development of body changes regarding statistical norm. The obtained results contribute to opportunities for modeling the running of this pathology. The results need to be applied in the creation of information system obesity diagnosis for further automation of this process. Automation of the obtained results using the diagnostic information system of obesity improves the quality of diagnosis of this disease. In the future, it is necessary to analyze in detail the representatives of different age and sex, the territorial and constitutional groups for proper evaluation of the process of formation for the various samples.